ANALYSIS OF NURSING CLINICAL PRACTICES WITH INNOVATIVE HAND AND FOOT MASSAGE INTERVENTION WITH LEMONGRASS OIL IN LOWERING BLOOD PRESSURE IN EMERGENCY HYPERTENSION PATIENTS WITH DECREASED CONSCIOUSNESS - Elsa Nur Janah; Alfi Ari Fakhrur Rizal; Annaas Budi Setyawan; Taharuddin, Taharuddin (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Hypertensive emergency is an emergency condition characterized by a significant increase in blood pressure accompanied by target organ damage, one of which is decreased consciousness. This condition can cause various nursing problems, including ineffective peripheral perfusion due to hemodynamic disorders and increased vascular resistance. This case study aims to analyze the clinical practice of nursing with the innovative intervention of Hand and Foot Massage with lemongrass oil in reducing blood pressure in hypertensive emergency patients with decreased consciousness in the ICU of Aji Muhammad Parikesit Tenggarong Regional Hospital. The method used is a case study with a comprehensive nursing care approach to client Mr. C who is treated in the ICU. The nursing process includes assessment, determination of nursing diagnosis, planning, implementation, and evaluation. The innovative intervention of Hand and Foot Massage with lemongrass oil was given for three consecutive days with a duration of 15–20 minutes per session, accompanied by blood pressure measurements before and after the intervention. After the innovative intervention of Hand and Foot Massage with lemongrass oil showed a decrease in systolic blood pressure with an average value of 15.67 mmHg and diastolic with an average value of 11 mmHg. In conclusion, the innovative hand and foot massage with lemongrass oil effectively lowers blood pressure. Therefore, healthcare workers can implement this innovative hand and foot massage intervention with lemongrass oil to lower blood pressure in hypertensive emergencies.